Stored carbon in the aboveground biomass of rubber (Hevea brasiliensis Müell. Arg.) plantations at different ages - López-Reyes, Liliana Y.; Domínguez-Domínguez, Marivel; Martínez-Zurimendi, Pablo; Zavala-Cruz, Joel; Gómez-Guerrero, Armando; Posada-Cruz, Saúl (Instituto de Ecología, A.C., 2016)
Hevea brasiliensis Müell. Arg plantations contribute to the reduction of atmospheric carbon dioxide by fixing carbon through photosynthesis and storing it in the tree components (leaves, branches, stems, barks and roots) and by their transformation to stabilized forms of soil organic matter. The objective of this study was to determine the stored carbon in the whole aboveground biomass in 5, 9, 15, 25, 32 and 51-year-old plantations, through a forest inventory and the use of allometric equations in Tabasco, Mexico. The stored carbon was determined using linear regression and mean values were analyzed by the Tukey test (p < 0.05) with the Statistical Analysis System (SAS) program. Results indicated that the carbon concentration varies with age; in 51-year-old plantation the stored carbon in stem was 192.32 Mg ha-1, in branches was 64.75 Mg ha-1 and in the whole tree was 257.07 Mg ha-1, while 5-year plantations had values of 16.65, 9.63 y 26.28 Mg ha-1, respectively. The results indicated that H. brasiliensis plantations can be considered a potential source of mitigation of climate change.